You looking at me?: Interpreting social cues in schizophrenia. Issue 1 (4th September 2015) - White, T. P.; Borgan, F.; Ralley, O.; Shergill, S. S.
Abstract : Background: Deficits in the perception of social cues are common in schizophrenia and predict functional outcome. While effective communication depends on deciphering both verbal and non-verbal features, work on non-verbal communication in the disorder is scarce. Method: This behavioural study of 29 individuals with schizophrenia and 25 demographically matched controls used silent video-clips to examine gestural identification, its contextual modulation and related metacognitive representations. Results: In accord with our principal hypothesis, we observed that individuals with schizophrenia exhibited a preserved ability to identify archetypal gestures and did not differentially infer communicative intent from incidental movements. However, patients were more likely than controls to perceive gestures as self-referential when confirmatory evidence was ambiguous. Furthermore, the severity of their current hallucinatory experience inversely predicted their confidence ratings associated with these self-referential judgements. Conclusions: These findings suggest a deficit in the contextual refinement of social-cue processing in schizophrenia that is potentially attributable to impaired monitoring of a mirror mechanism underlying intentional judgements, or to an incomplete semantic representation of gestural actions. Non-verbal communication may be improved in patients through psychotherapeutic interventions that include performance and perception of gestures in group interactions.